Clonal growth and plant species abundance - Herben, Tomáš; Nováková, Zuzana; Klimešová, Jitka (Annals of botany, 2014)
BACKGROUND AND AIMS: Both regional and local plant abundances are driven by species' dispersal capacities and their abilities to exploit new habitats and persist there. These processes are affected by clonal growth, which is difficult to evaluate and compare across large numbers of species. This study assessed the influence of clonal reproduction on local and regional abundances of a large set of species and compared the predictive power of morphologically defined traits of clonal growth with data on actual clonal growth from a botanical garden. The role of clonal growth was compared with the effects of seed reproduction, habitat requirements and growth, proxied both by LHS (leaf-height-seed) traits and by actual performance in the botanical garden. METHODS: Morphological parameters of clonal growth, actual clonal reproduction in the garden and LHS traits (leaf-specific area - height - seed mass) were used as predictors of species abundance, both regional (number of species records in the Czech Republic) and local (mean species cover in vegetation records) for 836 perennial herbaceous species. Species differences in habitat requirements were accounted for by classifying the dataset by habitat type and also by using Ellenberg indicator values as covariates. KEY RESULTS: After habitat differences were accounted for, clonal growth parameters explained an important part of variation in species abundance, both at regional and at local levels. At both levels, both greater vegetative growth in cultivation and greater lateral expansion trait values were correlated with higher abundance. Seed reproduction had weaker effects, being positive at the regional level and negative at the local level. CONCLUSIONS: Morphologically defined traits are predictive of species abundance, and it is concluded that simultaneous investigation of several such traits can help develop hypotheses on specific processes (e.g. avoidance of self-competition, support of offspring) potentially underlying clonal growth effects on abundance. Garden performance parameters provide a practical approach to assessing the roles of clonal growth morphological traits (and LHS traits) for large sets of species.
Keywords: druhová specificita; Česká republika; biologické modely; buněčné klony; biodiverzita; Clone Cells; Models, Biological; nepohlavní rozmnožování; vývoj rostlin; Species Specificity; Czech Republic; Plant Development; Reproduction, Asexual; Biodiversity